Tingkat Pemahaman Anggota Ikatan Mahasiswa Muhammadiyah Universitas Muhammadiyah Purworejo (IMM Umpwr) Terhadap Hukum Haram Komoditas Hewani: The Level of Understanding of Members of The Muhammadiyah Student Association of Purworejo Muhammadiyah University (IMM UMPWR) on The Haram Law of Animal Commodities - Miftahudin, Afrigh; Mudawaroch, Roisu Eny; Zulfanita, Zulfanita (Jurnal Riset Agribisnis dan Peternakan, 2024)
This study aims to determine the level of understanding of members of the Muhammadiyah Student Association of the University of Muhammadiyah Purworejo (IMM UMPWR) towards the Haram Law of Animal Commodities The sample determination technique in this study uses a survey. The sample in this study was 165 people. The data collection instrument used a questionnaire and Likert Scale. Data analysis uses quantitative descriptive. The results of the study showed the level of understanding of members of the Muhammadiyah Student Association of the University of Muhammadiyah Purworejo (IMM UMPWR) towards the Haram Law of Animal Commodities with an average score of 111.87. Most of the members of IMM UMPWR understand the haram law of animal commodities (pigs, blood, net animals, insects, disgusting animals, fanged wild animals)